No more aggregate NAEP studies? [editorial]. - Dorn, Sherman (Education Policy Analysis Archives, 2006)
This editorial reviews recent studies of accountability policies using National Assessment of Educational Progress (NAEP) data and compares the use of aggregate NAEP data to the availability of individual-level data from NAEP. While the individual-level NAEP data sets are restricted-access and do not give accurate point-estimates of achievement, they nonetheless provide greater opportunity to conduct more appropriate multi-level analyses with state policies as one set of variables. Policy analysts using NAEP data should still look at exclusion rates and the non-longitudinal nature of the NAEP data sets.